CO2 Solubility in Electrolyte Solution of Potassium Carbonate with the Addition of Promotor Amines (MDEA-DEA/ PZ-DEA) at Various Temperatures - Saidah Altway; Kuswandi Kuswandi; Iqwal Zulfetra; Firda Nuharani (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Carbon dioxide has a huge impact on the increase of greenhouse gas formation causing global warming and climate change. The most effective method to capture CO2 is chemical absorption using potassium carbonate (K2CO3) solution and amines as additive to enhance the absorption rate. CO2 solubilities in 30% of K2CO3 and 5% of the total composition of mixed methyldiethanolamine (MDEA)